2007
DOI: 10.1093/ije/dym129
|View full text |Cite
|
Sign up to set email alerts
|

Defining a minimum income for healthy living (MIHL): older age, England

Abstract: Objective evidence-based assessment of MIHL now is practicable but not presently as a basis of health and social policy in the UK or elsewhere apparently. Such assessment could also be an operational criterion of poverty and society's minimum income standards. The results suggest that inadequate income currently could be a barrier to healthy living for older people in England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 9 publications
3
40
1
3
Order By: Relevance
“…However, these studies had a global, rather than European, focus [35]. It appears that in the European countries considered here, more unequal distribution of income leads to a larger proportion of individuals with incomes less than the minimum required for healthy living [42,43], or below the poverty line. Thus, despite the overall wealth and level of economic development within a nation, income inequality increases the numbers of individuals within a country that have low vaccine coverage, engage in high-risk health behaviour, and have limited access to healthcare.…”
Section: Discussionmentioning
confidence: 94%
“…However, these studies had a global, rather than European, focus [35]. It appears that in the European countries considered here, more unequal distribution of income leads to a larger proportion of individuals with incomes less than the minimum required for healthy living [42,43], or below the poverty line. Thus, despite the overall wealth and level of economic development within a nation, income inequality increases the numbers of individuals within a country that have low vaccine coverage, engage in high-risk health behaviour, and have limited access to healthcare.…”
Section: Discussionmentioning
confidence: 94%
“…Morris found that the UK State Pension in 2007 provided only two-thirds of the Minimum Income for Healthy Living for an older person without disability, and that even the higher UK Pension Credit Guarantee was some £12 pounds per person per week less than MIHL (Morris et al, 2007). The weekly shortfall in income will be greater for older people with disability and impaired physical functioning.…”
Section: Discussionmentioning
confidence: 99%
“…These show the inadequacy of income from wages or welfare benefits to meet basic needs for healthy living, including food. In the UK this has been demonstrated for different household types, including young single men paid at or below the minimum wage (Morris et al, 2000), and those living on state pensions (Morris et al, 2007). Hirsch (2011) shows how recent cuts in social welfare have had disproportionate effect on different low income households' budgetary capacity; since food expenditure is what many with insufficient money to manage have to cut, it is extremely unlikely that such householders could purchase sufficient, appropriate food for health (Dowler, 2010).…”
Section: Case Studies Of Food Poverty and Insecurity: Uk/england And mentioning
confidence: 99%